Decrease in Self-Reported Tanning Frequency among Utah Teens following the Passage of Utah Senate Bill 41: An Analysis of the Effects of Youth-Access Restriction Laws on Tanning Behaviors - Rebecca G. Simmons; Kristi Smith; Meghan Balough; Michael Friedrichs (Journal of Skin Cancer)
Introduction. Adolescent use of indoor tanning facilities is associated with an increased risk in later development of melanoma skin cancers. States that have imposed age restrictions on access to indoor tanning generally show lower self-reported rates of indoor tanning than states with no restrictions, but currently no studies have assessed indoor tanning use before and after such restrictions. Methods. In 2013, we compared self-reported indoor tanning data collected in the Prevention Needs Assessment (PNA) survey in 2011 to PNA 2013 data. We also assessed predictors of continued tanning after passage of the bill. Results. Prior to the passage of Senate Bill 41, 12% of students reported at least one incident of indoor tanning in the past 12 months. After passage, only 7% of students reported indoor tanning in the past 12 months (P < 0.0001). Students who continued indoor tanning were more likely to be older and female and to engage in other risk behaviors, including smoking and alcohol use. Lower parental education levels were also associated with continued tanning. Conclusion. Indoor tanning restrictions showed beneficial impact on tanning rates in adolescents in Utah. Stricter restrictions may show even greater impact than restrictions that allow for parental waivers. Stronger enforcement of bans is needed to further reduce youth access.